Effects of Total Dietary Fiber on Cecal Microbial Community and Intestinal Morphology of Growing White Pekin Duck - Hao, Yongsheng; Ji, Zhanqing; Shen, Zhongjian; Wu, Yongbao; Zhang, Bo; Tang, Jing; Hou, Shuisheng; Xie, Ming (Frontiers in Microbiology, 2021)
The current study was to investigate the effects of total dietary fiber (TDF) on growth performance, cecal structure, cecal microbial community and short-chain fatty acids (SCFAs) profiles in the cecum of growing White Pekin ducks. A total of 108 male Pekin ducks of 14-d-old were randomly allocated and fed diets containing 12.4%, 14.7% and 16.2% TDF for 35 d. Each dietary treatment consisted of 6 replicates with 6 birds each. The results showed that 14.7% and 16.2% TDF treatments promoted growth performance relative to 12.4% TDF treatments (P < 0.05). 14.7% and 16.2% TDF treatments significantly elevated villus height, the ratio of villus height to crypt depth and muscle layer thickness of cecum, and lowered crypt depth compared with 12.4% TDF treatment (P < 0.05). Simultaneously, 14.7% and 16.2% TDF treatments up-regulated Claudin-1 mRNA expression of barrier genes in the cecum compared with 12.4% TDF (P < 0.05). Butyrate-producing bacteria like Oscillopiraceae affiliating to the phyla Firmicutes were observed as a biomarker in the 16.2% TDF. Higher concentration of butyrate in the cecum was obtained in the 14.7% TDF compared with 12.4% and 16.2% TDF (P < 0.05). The concentrations of isobutyrate, valerate and isovalerate in the cecum were significantly increased in the 16.2% TDF compared with 12.4% and 14.7% TDF (P < 0.05). Meanwhile, the abundance of genus UCG-005 and Enterococcus was positive correlations with isobutyrate and valerate (P < 0.05). However, the concentration of propionate in the cecum significantly decreased in 14.7% and 16.2% TDF treatments relative to 12.4% TDF treatments (P < 0.05). In summary, increasing TDF levels improved growth performance, cecal histomorphology and barrier function of meat ducks and it might be mediated by the changes of microbiota communities, especially bloom of SCFAs-producing bacteria, which facilitated the interaction between intestinal mucosa and microbiota.